Comparison of ribonucleotide sequences from the genome of vesicular stomatitis virus and two of its defective interfering particles. - Hagen, F S (1981)
RNA genomes from standard vesicular stomatitis virus and two defective interfering (DI) particles dI 0.33 (DI-T) and DI 0.52, were purified and digested with RNase T1. The resulting oligonucleotides were labeled at the 5' end with [32P]ATP and separated by two-dimensional electrophoresis in polyacrylamide gels. All of the major oligonucleotides containing 20 or more nucleotides were sequenced. Those oligonucleotides that were thought to be in common by their migration on polyacrylamide gels actually did have identical sequences. Those oligonucleotides thought to be unique to the DI RNAs either differed by only one nucleotide from oligonucleotides of the standard RNA or contained new sequences which were complementary to known sequences at the 5' end. These data indicate that RNAs from DI particles are not simple deletions but contain point mutations and additional complementary sequences.